A Highly Sensitive Fluorescent Sensor for Palladium and Direct Imaging of Its Ecotoxicity in Living Model Organisms. Issue 1 (15th October 2015) - Liu, Fei; Du, Juan; Xu, Meiying; Sun, Guoping
Abstract: Rhodamine is an ideal platform for fluorescence probes owing to its spiro‐lactam framework and excellent photochemical properties. Herein, a novel rhodamine‐based palladium fluorescent chemosensor, Rd‐Eb, showing a fast response time (3 min), high sensitivity for palladium species over other ions, and a low detection limit (1.91×10 −7 m ), was synthesized. It can act as an obvious colorimetric as well as a fluorescent "off/on" sensor for Pd 2+ . In addition, it is also an excellent sensor for in vivo imaging of Pd 2+ in zebra fish and Daphnia magna, illuminating the impact of palladium on organisms at different growth stages with respect to biological toxicology. Abstract : Thanks for your fast response : The novel rhodamine‐based palladium fluorescent chemosensorRd‐Eb shows a fast response time (3 min), a high sensitivity for palladium species over other ions, and a low detection limit (1.91×10 −7 m ). Furthermore, the probe was successfully used for imaging palladium in living organisms.